2021
DOI: 10.1016/j.jvs.2020.08.138
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and individual patient data meta-analysis of heart failure as a rare complication of traumatic arteriovenous fistulas

Abstract: Objective: Traumatic arteriovenous fistulas (AVFs) are rare. The vast majority occur secondary to penetrating injuries. High-output cardiac failure is a well-recognized serious complication of AVFs, associated with high morbidity and mortality. The objective of the present study was to identify predictors of heart failure (HF) in patients with traumatic AVF.Methods: Both PubMed/MEDLINE (Ovid) and CINAHL were searched (up to June 2019) for studies reporting individual patient data on the clinical and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…It has been shown that heart failure secondary to AVF commonly occurs after extensive latency periods and that the risk of heart failure increases with an increasing AVF feeding artery diameter. 10 Accordingly, early recognition of the AVF could restore physiological haemodynamic conditions and therefore prevent the risk of heart failure and enhance patient outcomes. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that heart failure secondary to AVF commonly occurs after extensive latency periods and that the risk of heart failure increases with an increasing AVF feeding artery diameter. 10 Accordingly, early recognition of the AVF could restore physiological haemodynamic conditions and therefore prevent the risk of heart failure and enhance patient outcomes. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Accordingly, early recognition of the AVF could restore physiological haemodynamic conditions and therefore prevent the risk of heart failure and enhance patient outcomes. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted January 14, 2022. ; https://doi.org/10.1101/2022.01. 13.476153 doi: bioRxiv preprint the coronary sinus (7%), the left atrium (5%) and the left ventricle (less than 3%) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these cardiac congenital defects should not be mistaken for isolated connections existing between blood vessels and /or cardiac cavities that result from surgical interventions, traumatic events or infections (e.g. endocarditis), which are often referred-to as 'fistulae' and even 'pseudoaneurisms' [11][12][13] . Indeed, congenital CAFs are true anomalies that derive from abnormal embryogenesis and, as such, they frequently associate to other forms of CHD, including Tetralogy of Fallot, atrial and ventricular septal defects, persistent ductus arteriosus, pulmonary atresia and left ventricular noncompaction, among others 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Statistical limitations to knowing the odds of heart failure for patients with traumatic arteriovenous fistulas I read the article by Wenzl et al 1 "A systematic review and individual patient data meta-analysis of heart failure as a rare complication of traumatic arteriovenous fistulas" with great interest. Understanding the odds of patients developing severe complications is a worthy endeavor.…”
mentioning
confidence: 99%